2013
DOI: 10.1177/0954411912471495
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the grain size on the in vivo degradation behaviour of the magnesium alloy LAE442

Abstract: The aim of this study was to investigate the differences in the in vivo degradation behaviour of magnesium implants with various grain sizes and damaged surfaces. For this purpose, three different LAE442 magnesium implants were produced: cast, single and double extruded implants, in order to obtain different grain sizes. Furthermore, defects were positioned on the surfaces of some of the single extruded implants. The initial stability was determined. Four pins of each implant material were implanted into rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 34 publications
6
39
0
Order By: Relevance
“…Also Ullmann et al [86] found no significant changes in LANd442 implant volume but a significant decrease in density after 26 weeks. Additionally, they reported a significant decrease in maximum force as corrosion magnesium usually undergoes if exposed to chloride ions in nonoxidizing solutions [87] and was observed by several authors examining different magnesium-based alloys in vivo [44] or in vitro [88]. However, others did not observe signs of pitting on the surface of LAE442 pins after in vivo degradation [83,84].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Also Ullmann et al [86] found no significant changes in LANd442 implant volume but a significant decrease in density after 26 weeks. Additionally, they reported a significant decrease in maximum force as corrosion magnesium usually undergoes if exposed to chloride ions in nonoxidizing solutions [87] and was observed by several authors examining different magnesium-based alloys in vivo [44] or in vitro [88]. However, others did not observe signs of pitting on the surface of LAE442 pins after in vivo degradation [83,84].…”
Section: Discussionmentioning
confidence: 80%
“…Histological examinations of liver, kidney and spleen after implantation of different magnesium-based alloys (AZ31, MgZn) also did not give any hint on systemic toxicity [29,32]. In previous investigations, the magnesium-based LAE442 alloy has already proven its favorable properties in rabbits such as a comparatively slow and uniform degradation, a good biocompatibility and a high initial stability [43][44][45][46][47]. However, only little is known about the local (bone) and systemic (internal organs) effects caused by the implantation of large amounts of biodegradable implant material in long bones.…”
Section: Introductionmentioning
confidence: 93%
“…One way to achieve this could be through grain refinement, as has 369 been previously demonstrated with Mg alloy LAE442 [28]. as improved passive film formation due to increased activity of 378 reduced grain size area, and consequently, better adhesion due to 379 increased grain boundary density [29].…”
mentioning
confidence: 95%
“…After the surgical trauma, the oxygen tension and local pH would be reduced and re- sulted in fast corrosion. Furthermore, Ulmann et al [43] found defects on the surface of intramedullary implantations of LAE442 alloys and the defects led to the faster initial corrosion than the intact implants. In the present study, the implants were tapped in the narrow predrilled bone tunnel, which could have scratched the implant's surface and caused fast initial corrosion [44].…”
Section: In Vitro and In Vivo Biocompatibility Of Mg-zn-ca Alloymentioning
confidence: 99%